Exploring Fiscal Policy and Diversification Effects on Nigeria's Long-Term Economic Growth - ABANG, Samuel Oweh; ABUH-AMASI, Scholastica Ashibebonye; ARASOMWAN, Kenneth Оnaiwu; AYODELE, Oluwafemi; ABANG-SAMUEL, Loveth Ifeoma (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study investigates the long-term impact of fiscal policy and economic diversification on Nigeria’s economic growth, with a focus on understanding their interrelationships and effectiveness in driving sustainable development.Methodology:Using time-series data from 1983 to 2024, the study employs the Autoregressive Distributed Lag (ARDL) bounds testing approach to examine both the short- and long-run dynamics among key fiscal variables, diversification indicators, and real GDP growth.Findings:Empirical findings reveal a significant long-run relationship between fiscal policy instruments, particularly government expenditure and tax revenue—and economic growth. The results highlight the importance of strategic fiscal management and the need to accelerate diversification policies to reduce reliance on oil revenues and promote inclusive development.Implication:The study recommends that fiscal authorities adopt more growth-oriented expenditure frameworks and broaden the revenue base by enhancing non-oil sectors such as agriculture, manufacturing, and services. This research contributes to the policy discourse on fiscal sustainability and structural economic reform in Nigeria.